ARTIFICIAL INTELLIGENCE MISUSE AND ITS IMPACT ON MEDICAL STUDENTS’ KNOWLEDGE QUALITY AND CLINICAL THINKING SKILLS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
In recent years, artificial intelligence (AI) has become an innovative tool in medical education and practice. However, misuse of AI or its uncritical application may negatively affect medical students’ knowledge quality and clinical thinking skills. Research shows that improper AI use weakens active learning and critical thinking among medical students, increases passivity, and raises the risk of making decisions based on inaccurate information. At the same time, proper AI integration can improve educational efficiency, but clear scientific guidelines and ethical standards are required.